The potential of urban green spaces to face contemporary socioenvironmental challenges - Vidal, Diogo Guedes (2019)
Cities and urban spaces are, in our days, places of the most diversified dynamics. Since the beginning of the XX century, urbanization, demographic explosion (Kondo et al., 2018; UN, 2014) and consumer behaviour have affect environment and, consequently, human health. The connection between environment and human health is undeniable and as well as the impacts of environmental pollution, namely air pollution, on the population’s health (Raaschou-Nielsen et al., 2016; Pope et al., 2002). Towards this evidence, it is an urgent need that cities adopt strategies in order to face these contemporary social and environmental problems. Several studies had focused on the potentials of Urban Green Spaces (UGS), aiming to prove their capability to mitigate air pollution, rejuvenate urban areas, control stress and mental health, minimize ischemic diseases and empower social participation (Seymour, 2016; James et al., 2015; Haluza et al., 2014; Bowler, et al., 2010).